Supply Chain Collaboration in Tourism: A Transaction Cost Economics Analysis - Pairach Piboonrungroj; Stephen Michael Disney (International Journal of Supply Chain Management, 2015)
This paper explores inter-firm collaboration in a tourism supply chain via transaction cost economics using a single case-study method. We focus on supply chain collaboration between a hotel, and its food and beverage suppliers. The transaction costs found consist of the search cost and cost of quality checking. Search cost exists due to bounded rationality of the firm. This is influenced by asymmetric information. The cost of quality checking incurs because the firm perceives that its suppliers may behave opportunistically. It is revealed that trust could reduce transaction cost of the tourist operators.